Consistency of Hemoglobin A1c Testing and Cardiovascular Outcomes in Medicare Patients With Diabetes - Goodney, Philip P. (J Am Heart Assoc, 2016)
BACKGROUND: Annual hemoglobin A1c testing is recommended for patients with diabetes mellitus. However, it is unknown how consistently patients with diabetes mellitus receive hemoglobin A1c testing over time, or whether testing consistency is associated with adverse cardiovascular outcomes. METHODS AND RESULTS: We identified 1 574 415 Medicare patients (2002–2012) with diabetes mellitus over the age of 65. We followed each patient for a minimum of 3 years to determine their consistency in hemoglobin A1C testing, using 3 categories: low (testing in 0 or 1 of 3 years), medium (testing in 2 of 3 years), and high (testing in all 3 years). In unweighted and inverse propensity‐weighted cohorts, we examined associations between testing consistency and major adverse cardiovascular events, defined as death, myocardial infarction, stroke, amputation, or the need for leg revascularization. Overall, 70.2% of patients received high‐consistency testing, 17.6% of patients received medium‐consistency testing, and 12.2% of patients received low‐consistency testing. When compared to high‐consistency testing, low‐consistency testing was associated with a higher risk of adverse cardiovascular events or death in unweighted analyses (hazard ratio [HR]=1.21; 95% CI, 1.20–1.23; P<0.001), inverse propensity‐weighted analyses (HR=1.16; 95% CI, 1.15–1.17; P<0.001), and weighted analyses limited to patients who had at least 4 physician visits annually (HR=1.15; 95% CI, 1.15–1.16; P<0.001). Less‐consistent testing was associated with worse results for each cardiovascular outcome and in analyses using all years as the exposure. CONCLUSIONS: Consistent annual hemoglobin A1c testing is associated with fewer adverse cardiovascular outcomes in this observational cohort of Medicare patients of diabetes mellitus.